2014
DOI: 10.1039/c4ce00256c
|View full text |Cite
|
Sign up to set email alerts
|

Mesocrystals as a class of multifunctional materials

Abstract: Mesocrystals that consist of crystallographically aligned individual building blocks and controlled level of porosity in between exhibit unique structures and multifunctional behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 199 publications
(196 reference statements)
0
40
0
Order By: Relevance
“…Nevertheless, in comparison to structures formed by oriented attachment, the nanoscale building blocks in mesocrystals remain stabilized, typically by an organic coating, and do not fully fuse together. For an extensive overview of non‐classical crystallization mechanisms, we refer the reader to some excellent recent reviews and to a textbook . It seems that particle‐based crystallization pathways play a particularly important role in nonaqueous environment.…”
Section: Crystallization Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, in comparison to structures formed by oriented attachment, the nanoscale building blocks in mesocrystals remain stabilized, typically by an organic coating, and do not fully fuse together. For an extensive overview of non‐classical crystallization mechanisms, we refer the reader to some excellent recent reviews and to a textbook . It seems that particle‐based crystallization pathways play a particularly important role in nonaqueous environment.…”
Section: Crystallization Mechanismsmentioning
confidence: 99%
“…[27] In some cases,m esocrystals are difficult to discriminate from classically grown single crystals,e specially when the nanoscale buildingb locks are perfectly oriented and partially fused. Nevertheless, in comparison to structures formed by oriented attachment, the nanoscale building blocks in mesocrystals remain stabilized, typically by an organic coating, and do not fully fuse together.F or an extensive overview of non-classical crystallization mechanisms, we refer the readert os ome excellent recentr eviews [25,27,28,[236][237][238][239][240] and to at extbook. [241] It seems that particle-based crystallization pathways play ap articularly important role in nonaqueouse nvironment.…”
Section: Crystallization Mechanismsmentioning
confidence: 99%
“…Anyhow, whether mesocrystals are considered for application in photocatalyisis, solar energy conversion or optoelectronics, they need to be well characterized, and compared with their nanocrystalline and single-crystal counterparts. [24][25][26] Please do not adjust margins Please do not adjust margins In order to check if it is possible to use the same general method of synthesis for the other three-component semiconductors, we have chosen to synthesize ZIS, another semiconductor from II-III 2 -VI 4 family. As Bae et al 28 suggested, Cd 2+ has weaker binding energy with oleic acid then Zn 2+ , hence the same principles of OLAM usage was tried for synthesis of ZnIn 2 S 4 .…”
Section: Cdin 2 Smentioning
confidence: 99%
“…It is inferred that the anisotropic dissolution of NH 4 TiOF 3 can chemically convert to TiO 2 mesocrystal (TMC) during the topochemical transformation, accompanying with N and F releasing [13][14][15][16]. As a new class of porous building blocks oriented assembly of nanocrystals, the obtained TMC with a well-defined crystal shape significantly enhances the charge separation with remarkably long-lived charges and exhibits excellent photocatalytic activities http compared with TiO 2 nanocrystals and commercial P25 [17][18][19][20]. It is a great of significance to introduce the dopant simultaneously from the original precursors or intermedium during the synthesis, without affecting the nucleation and growth of TMC.…”
Section: Introductionmentioning
confidence: 98%